Cover Picture: Macromol. Mater. Eng. 9/2014. Issue 9 (September 2014) - Kwon, Jinuk; Kim, Jinyoung; Yoo, Taewon; Park, Dongmyung; Han, Haksoo
<x xml:space="preserve">Abstract</x> Cover: Polyimide‐based spherical aerogel microparticles, a novel form of polyimide aerogels, are fabricated. The existing polyimide aerogels, published earlier by other institutions, can only be fabricated in film shapes. The aerogel microparticles proposed in this study have an advantage over film‐shaped aerogels because the microparticles can be easily employed for thermal insulation, drug release, and catalyst support. Further details can be found in the article by J. Kwon, * J. Kim, T. Yoo, D. Park, and H. Han* on page 1081. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>